The Effect of Soaking on CBR Values in Soft Soils Stabilized with Stone Ash and Sand - Juliana, Nova; Bawadi, Nor Faizah; Endriani, Debby (International Journal of Integrated Engineering, 2024)
Constructing in the soft soil is necessary to improve. The improvement of soft soil by mixing natural materials, namely stone ash and sand, reduces the impact of environmental damage when using chemical additives. Variations of materials mixture were 0%, 5%, 10%, 15%, and 20%. To determine the strength of the soil that has been mixed with natural materials, a test called the California Bearing Ratio (CBR) is carried out. The CBR laboratory test illustrates the conditions that will occur in the field. This CBR test was carried out using soaked and un-soaked methods. For testing by soaking, mixed variations of 0% and 5% obtained a low CBR value. The highest was 10% mixed variation and decreased to 15% and 20%. The CBR test without soaking had the highest CBR value at 5% mixture variation and the lowest at 0%. Adding a mixture variation above 5% causes the CBR value to decrease slowly. The results of the tests show that soaking the soil makes the soil condition saturated with water so that the resulting CBR value becomes very low.